Bamboo fibre composites: Potential and challenges - Liew, Yu Xuan; Khong, Sheh Ching; Yee, Jia Jun; Chin, Siew Choo; Tee, Kong Fah (Nova Science Publishers, 2023)
This chapter discusses the possible use of bamboo fibre composites in structural applications, highlighting how the performance of the composite can be modified by the bamboo species, fibre extraction process, and composite fabrication method. Bamboo fibre composites are affected by parameters such as species, age, and extraction processes. Apart from that, the performance of bamboo fibre composites is influenced by the matrix, which consists of thermosetting and thermoplastic resins.